Comparison of efficacy, safety, and patient satisfaction between thermal ablation, conventional/open thyroidectomy, and endoscopic thyroidectomy for symptomatic benign thyroid nodules. (31st December 2022) - Bo, Xiao-Wan; Lu, Feng; Yu, Song-Yuan; Yue, Wen-Wen; Li, Xiao-Long; Hu, Man; Wu, Li-Li; Lv, Zhu-Ying; Sun, Li-Ping; Xu, Hui-Xiong
Abstract: Purpose: Thermal ablation (TA) is a minimally invasive treatment method for symptomatic benign thyroid nodules (BTNs). This study aimed to evaluate the value of TA by comparing the efficacy, safety, and patient satisfaction with conventional/open thyroidectomy (ConT) and endoscopic thyroidectomy (ET) for symptomatic BTNs. Methods: Patients with symptomatic BTNs who underwent ConT, ET, or TA therapy between January 2018 and January 2020 were included. Pre-operation data of the two comparisons (TA vs. ConT and TA vs. ET) was balanced using propensity score matching. The technique efficacy (volume reduction ratio ≥50%), nodule disappearance, and regrowth rate were calculated after ablation. The operation and hospitalization time, medical cost, complications, post-operative symptoms, and cosmetic scores were recorded and compared. Patient satisfaction was evaluated using a telephone survey. Results: After a median 19-month follow-up (range, 12–36 months), the technique efficacy rate, nodule disappearance, and regrowth rate were 93.2% (119/129), 6.8% (10/129), and 0.8% (1/129), respectively. Operation time, hospitalization time, and medical costs were less for patients in the TA group than for patients in the ConT and ET groups (all p < 0.001). The incidence of complications, post-operative symptoms, cosmetic scores, and overall satisfaction were not significantly different among groups (all p > 0.05). Post-operative hypothyroidism was less frequent in the TA group than in the ConT and ET groups (all p < 0.05). Conclusions: Compared to ConT and ET, TA has comparable efficacy, safety, and patient satisfaction and exhibits greater protection of thyroid function for the treatment of symptomatic BTNs.